2003
DOI: 10.1090/s0002-9947-03-03085-x
|View full text |Cite
|
Sign up to set email alerts
|

The central limit problem for convex bodies

Abstract: Abstract. It is shown that every symmetric convex body which satisfies a kind of weak law of large numbers has the property that almost all its marginal distributions are approximately Gaussian. Several quite broad classes of bodies are shown to satisfy the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
225
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(233 citation statements)
references
References 9 publications
7
225
0
1
Order By: Relevance
“…Our idea is to put K in another position, namely Löwner's minimal diameter position, in which we show in Proposition 4.10 that the diameter is not larger than C λ n 1−λ , where λ depends only on α, the 2-convexity constant of K and C > 0 is a universal constant. We conclude Proposition 1.5 by proving a version of a Theorem from [ABP03] about the existence of Gaussian marginals, where the assumption of being in isotropic position is removed (see Theorem 5.3). Further developments on the existence of Gaussian marginals of uniformly convex bodies are discussed in [Mil06b].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Our idea is to put K in another position, namely Löwner's minimal diameter position, in which we show in Proposition 4.10 that the diameter is not larger than C λ n 1−λ , where λ depends only on α, the 2-convexity constant of K and C > 0 is a universal constant. We conclude Proposition 1.5 by proving a version of a Theorem from [ABP03] about the existence of Gaussian marginals, where the assumption of being in isotropic position is removed (see Theorem 5.3). Further developments on the existence of Gaussian marginals of uniformly convex bodies are discussed in [Mil06b].…”
Section: Introductionmentioning
confidence: 70%
“…The motivation for this requirement comes from [ABP03], where it was shown that if an isotropic 2-convex body has small-diameter in the above sense, then most of its marginals are approximately Gaussian (see [ABP03] or Section 5 for more details). It is easy to check that this requirement is indeed satisfied by all the l n p unit balls for 1 < p ≤ 2 (normalized to have the appropriate volume).…”
Section: Sketch Of Proofmentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 1.1 (Generalized from [ABP03]). Assume that (1.1) holds for a centrally-symmetric convex body K. Then for any 0 < δ < c:…”
Section: Introductionmentioning
confidence: 99%